Urban hydrology, hydraulics, and stormwater quality : engineering applications and computer modeling - Akan, A. Osman (J. Wiley & Sons, 2003)
Annotation A practical introduction on today's challenge of controlling and managing the water resources used by and affected by cities and urbanized communities. The book offers an integrated engineering approach, covering the spectrum of urban watershed management, urban hydraulic systems, and overall stormwater management. Each chapter concludes with helpful problems. Solutions Manual available to qualified professors and instructors upon request. Introduces the reader to two popular, non-proprietary computer-modeling pro-grams: HEC-HMS (U.S. Army Corps of Engineers) and SWMM (U.S EPA).
Keywords: Urban hydrology.; Urban runoff -- Management.; Water quality management.; elektronické knihy; electronic books